Report of the Task Force on Skill Development - Planning Commission (Planning Commission, 2007)
Vocational Education and Training (VET) has been supply driven in this country, largely on account of Government’s focus on the -welfare of its citizens and a cultural mindset among our people which does not place a premium on blue collar jobs and the development of professional skills. The proposed Mission on Skill Development can address this issue through a major campaign. The central paradox is that while the country faces a shortage of skilled personnel on the one hand there is widespread unemployment of the ‘educated’ on the other. At the very outset, therefore the Task Force would like to emphasise that the present state of affairs is not acceptable for a country which seeks to become a knowledge power, a global service and manpower provider and a leading industrial nation. There has to be a paradigm shift in the national policy on skill development with the private sector playing a lead role instead of the government, as they are the job providers.
Planning Commission Government of India
Planning Commission Government of India